The Effect Of The Use Of Brown Rice Flour (Oryza Nivara) In The Making Of Almond Crispy On Physical Properties And Consumer Acceptance) - Rhiska Ayu Morendra; Sachriani Sachriani; Nur Riska (Universitas Negeri Padang, 2021)
This study was intended to determine the that the use of brown rice flour on the physical qualities perceived by consumers. This research begins with the manufacture of brown rice flour, where brown rice is soaked in water, then dried, then milled. The brown rice flour used was 70% (P1), 80% (P2) 90% (P3). In terms of dough diameter, thickness assessment of physical properties by measuring weight, assessment of consumer intake was examined organoleptically by 3 experts (general education teacher) 25 medium training specialists (culinary students). Based on the results of the Anova test, the use of brown rice flour did not affect the physical qualitiess of smooth almonds. Friedman test results show that the use of brown rice flour has a significant effect on color, but has no effect on aroma, taste, texture, horsepower. The test result = 0.05 indicates that P2 is the most recommended color product because it has the highest value. Products with P2 processing are recommended as the best almonds in terms of physical acceptability by consumers.